2015
DOI: 10.3402/qhw.v10.28717
|View full text |Cite
|
Sign up to set email alerts
|

Empowered to gain a new foothold in life—A study of the meaning of participating in cardiac rehabilitation to patients afflicted by a minor heart attack

Abstract: This study aimed to investigate what it means to patients afflicted by a minor heart attack to participate in cardiac rehabilitation (CR). CR is well-established internationally to support patients towards moving forward in satisfying, healthy, and well-functioning lives. Studies indicate that patients achieve improvement in quality of life when participating in CR. However, knowledge of how patients are supported during CR is sparse. Moreover, knowledge of what participating in CR means to patients afflicted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 43 publications
2
24
0
Order By: Relevance
“…From the findings in our study, nurses ought to work with a more recovery-oriented holistic approach (Davidson, 2008 ; WHO, 1986 ) where behavioural, social, and psychological dimensions are taken into account. This is in line with a recent study (Simony et al, 2015 ) that showed that recovery after an MI, for both women and men, is a matter of finding new values in lives through focusing on individual needs and subjective well-being.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…From the findings in our study, nurses ought to work with a more recovery-oriented holistic approach (Davidson, 2008 ; WHO, 1986 ) where behavioural, social, and psychological dimensions are taken into account. This is in line with a recent study (Simony et al, 2015 ) that showed that recovery after an MI, for both women and men, is a matter of finding new values in lives through focusing on individual needs and subjective well-being.…”
Section: Discussionsupporting
confidence: 91%
“…Research has also shown that women value the emotional support and social interaction during CRP more than men and men appreciate the opportunity for information exchange more than women (Barlow, Turner, & Gilchrist, 2009 ). However, in more recent studies both women and men describe that they want to be supported in finding new values in life (Kazimiera Andersson, Borglin, & Willman, 2013 ; Pryor et al, 2014 ; Simony et al, 2015 ), which is also in line with our women's descriptions. In our study, we have not investigated differences between genders, but our result does not confirm the traditional gender-role patterns because the women also described values that seem to be more suitable for males.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Secondly they viewed it as an important factor to help them make a positive recovery. An empathic approach from health professionals combined with the provision of support helped to build a strong professional-patient relationship which in turn increased patients' receptivity to lifestyle changes (Hansen & Nelson, 2011;Kristofferzon et al, 2007;Simony et al, 2015;Treloar, 1997;White et al, 2010;Woodard et al, 2005;Wright et al, 2001; (Simony et al, 2015) Patient participants described the positive aspects of consultations in which health professionals communicated that they understood the patient's perspective and why they might behave in a particular way. The provision of individualized support and reassurance, active listening, positive facial expressions (smiling) and physical contact (e.g.…”
Section: Empathic Interactionsmentioning
confidence: 99%